Kinetics, products, and mechanism for the reaction of E−CF3CH=CHC2F5 with OH radicals in gas phase and atmospheric implications. (July 2018) - Guo, Qin; Zhang, Ni; Uchimaru, Tadafumi; Chen, Liang; Quan, Hengdao; Mizukado, Junji
Abstract: E –CF3 CH=CHC2 F5 is a promising substance that could be used as high temperature bump working fluid. In this study, the rate constants ( k 1 ) for the reaction of E −CF3 CH=CHC2 F5 with OH were measured by the relative rate method: k 1 (298 K) = (9.10 ± 0.29) × 10 −14 and k 1 (253–328 K) = (7.56 ± 0.88) × 10 −13 exp [−(632 ± 35)/T] cm 3 molecule −1  s −1 . The atmospheric lifetime of E −CF3 CH=CHC2 F5 was estimated to be 127 d, while its radiative efficiency (RE) was evaluated to be 0.198 W m −2  ppb −1 . The estimated POCPs of E −CF3 CH=CHC2 F5 were estimated to be 0.5 and 0.2 for North-west European and USA urban conditions, respectively. The 20, 100, and 500-year time horizon global warming potentials (GWPs) of E −CF3 CH=CHC2 F5 were estimated to be 73, 20, and 6, respectively. CF3 OOOCF3, CF3 OOOC2 F5, COF2, CO, and CO2 were identified as the carbon-containing products following the degradation of E –CF3 CH=CHC2 F5 . Highlights: k OH (253–328K) of E –CF3 CH=CHCF2 CF3 were estimated by relative rate method. The products and mechanism of the OH-initiated oxidation were investigated. The infrared spectrum, radiative efficiency and atmospheric lifetime were obtained. POCP and GWPs were evaluated and the environmental impacts were discussed.